Response of Italian ryegrass (Lolium multiflorum Lam.) to coffee waste application on a humid tropical sandy soil. (8th November 2012) - Kasongo, R. K.; Verdoodt, A.; Kanyankogote, P.; Baert, G.; Van, E.
Abstract A greenhouse experiment was conducted to study the effect of coffee waste (CW) application on growth and mineral nutrition of Italian ryegrass in a tropical Arenosol. Dry CW was applied at three rates (5, 10, 20 t/ha) and thoroughly mixed with topsoil (0–25 cm), placed in pots and seeded with Italian ryegrass (Lolium multiflorum Lam.) according to a completely randomized design with six replicates. The application of CW greatly stimulated uptake of Ca, Mg, K, N and P, resulting in a significantly increased dry matter (DM) production over three consecutive cropping cycles. DM increases of at least 52, 87 and 81% compared with the unamended controls were obtained for the first, second and third cuts, respectively. Soil analysis after cultivation found that all CW‐amended soils still contained available macronutrients (Ca, Mg, K, N), which could produce residual effects in subsequent crops. Furthermore, CW application increased soil pH owing to its liming effect. This brought about an increase in cation exchange capacity with substantial reduction in phytotoxic Al and a decrease in availability of a number of metals (Cu, Zn, Mn and Fe) and significantly reduced their uptake by ryegrass. The study reveals a high potential of CW to improve the fertility of sandy soils in the humid tropics.